Piceatanol: Anti-Cancer Compound From Gewang Seed Extract - Leny Heliawati & , Agus Kardinan,Tri Mayanti, Roekmi-ati Tjokronegoro (Journal of Applied Pharmaceutical Science, 2015)
Piceatannol (Compound 1), brownish white solids compound, is a stilbene compound has been isolated from methanol seeds extract of Corypha utan Lamk. Isolation and purification conducted by chromatographic methods. Structure elucidation deduced on the basis of spectroscopic data (UV spectrometer, FTIR, NMR and HRMS). MTT assay method of cytotoxicity activity showed that Compound 1 has a very strong cytotoxic activity against Murine leukemia P-388 cell lines with IC50 value 1.56 ppm.
Keywords: Corypha utan Lamk, Murine leukemia P-388, Cytotoxic, Chromatography, Piceatannol.